(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The adoption of the Primary Health Care Under One Roof (PHCUOR) initiative serves as a crucial approach to tackle the complex challenges encountered by primary healthcare systems worldwide. This paper explores the historical background, present difficulties, and possible remedies related to primary healthcare in Nigeria, with a particular emphasis on the PHCUOR model. By referencing important papers like the Alma Ata Declaration and current research, we highlight the importance of Primary Health Care (PHC) in public health systems. This emphasis how PHC helps to promote health equity and achieve universal health coverage. The PHCUOR model is a progressive approach to healthcare delivery that promotes the consolidation of different services under a single administrative entity in order to enhance the coordination and comprehensiveness of care. The effectiveness of the strategy in improving access, boosting coordination, and delivering cost-effective treatment is demonstrated by several case studies from Anambra and Lagos States. In order to fully harness the potential of PHCUOR (Primary Health Care Under One Roof) in Nigeria, it is crucial for policymakers, healthcare providers, and stakeholders to give utmost importance to the establishment of policy frameworks that are supportive, the development of infrastructure, the enhancement of capacity, and the implementation of sustainable finance mechanisms. Nigeria may enhance its primary healthcare system, enhance health outcomes, and promote health equity for all its residents by adopting these initiatives and proposals.